Integrated and enhanced datasets on food security and household coping strategies in the G5 Sahel Countries (2018-2023) - Marivoet, Wim; Hema, Aboubacar (International Food Policy Research Institute, 2024)
This report describes the methodology and output behind the integration and enhancement of nationally representative household surveys on food security and coping strategies implemented in the G5 Sahel countries between 2018 and 2023. Whereas the data integration process involves the harmonization of variables across multiple cross-sectional surveys, the enhancement procedure focuses on adding shock data on multiple dimensions of political violence, food price anomalies, and climate- and weather-related events. Despite shortcomings in data quality and exhaustivity, the resulting datasets represent a unique playground to study the interaction between shocks and stressors on the one hand and household coping strategies and their impact on food security on the other hand.